Parasites found in surgical pathology: the institutional experience - Shah, Khushbu P.; Patel, Mandakini M. (International Journal of Research in Medical Sciences, 2019)
Background: Parasitic infestation has a worldwide prevalence and it affects almost all age groups and both the sexes. The incidence of these infections is slowly rising in today’s era. Parasites are mainly found in stool samples but due to increase in a immunocompromised state now a days, tissue parasitaemia has increased globally necessitating more such type of studies. Parasite found in surgical pathology either incidentally or in clinically suspicious cases not only improves morbidity but also saves clinician’s time and patient’s money. Methods: A retrospective-cross sectional study is done based on histomorphological and cytomorphological evaluation of 25 cases diagnosed at The Department of pathology, New Civil Hospital Surat from January 2015 to January 2017. Results: Most common parasite seen was Echinococcus presenting as hydatid cyst in liver followed by filariasis. Most common age group affected was 0-20 years of age. Most common intestinal parasite found in our study was Entamoeba histolytica. Patients presented with variety of symptoms. Conclusions: Distribution of parasite in tissue section in relation to frequency, age, sex, various system involvements and its correlation with clinical symptoms are analyzed in our study.